LONGITUDINAL FOLLOW-UP OF CHOROIDAL GRANULOMAS WITH INDOCYANINE GREEN ANGIOGRAPHY AND OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY: A Lesion-Based Analysis. Issue 5 (May 2022) - Parrulli, Salvatore; Invernizzi, Alessandro; Monteduro, Davide; Zicarelli, Federico; Oldani, Marta; Staurenghi, Giovanni; Woodstock, Elizabeth; Hay, Steven; Neri, Piergiorgio; Pichi, Francesco
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: To investigate choroidal granulomas visualized by indocyanine green angiography (ICGA) and optical coherence tomography angiography (OCTA) in response to treatment. Methods: Ten eyes of eight patients with tubercular, sarcoid, or Vogt–Koyanagi–Harada-associated choroidal granulomas were evaluated in this multicentric study. All patients underwent ICGA and OCTA at baseline, 1, and 3 months after treatment onset. Granulomas were identified as hypofluorescent lesions on intermediate ICGA phases. Late ICGA behavior and OCTA visualization were assessed. Results: On baseline intermediate ICGA, 222 choroidal granulomas were detected. Overall, 174/222 granulomas were detected on baseline OCTA images. At 1 month, 28% of lesions were healed and 48 late ICGA hyperfluorescent lesions were identified. At 3 months, 63% of baseline lesions were healed, with 33 persistent late hyperfluorescent lesions. Optical coherence tomography angiography sensitivity was reduced at 1 and 3 months compared with baseline. Some flow-voids detected on OCTA at 1 and 3 months did not correspond to any visible lesion on ICGA. Conclusion: Different healing behaviors of choroidal granulomas were identified combining ICGA and OCTA analysis. Late ICGA hyper-fluorescent lesions may be the consequence of a possible fibrotic shift. Structural changes in the choroid may persist after active granulomas resolution resulting in persistent flow voids on OCTA.